2022
DOI: 10.3390/molecules27123671
|View full text |Cite
|
Sign up to set email alerts
|

The Intervention of Prebiotics on Depression via the Gut–Brain Axis

Abstract: The imbalance of intestinal microbiota can cause the accumulation of endotoxin in the main circulation system of the human body, which has a great impact on human health. Increased work and life pressure have led to a rise in the number of people falling into depression, which has also reduced their quality of life. The gut–brain axis (GBA) is closely related to the pathological basis of depression, and intestinal microbiota can improve depressive symptoms through GBA. Previous studies have proven that prebiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 136 publications
0
10
0
Order By: Relevance
“…In fact, several gut microbiota-based interventions improved the negative effects of chronic stress in rodents. For instance, the administration of live bacterial strains (probiotics) and host-indigestible dietary fibers (prebiotics) that can be fermented by gut microbiota ,, displayed beneficial effects. However, several studies have also reported no effect of these microbiome-based therapeutics on depressive-like behavior .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, several gut microbiota-based interventions improved the negative effects of chronic stress in rodents. For instance, the administration of live bacterial strains (probiotics) and host-indigestible dietary fibers (prebiotics) that can be fermented by gut microbiota ,, displayed beneficial effects. However, several studies have also reported no effect of these microbiome-based therapeutics on depressive-like behavior .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that about one-third of patients with depression may encounter TRD in their lives. , Thus, the discovery of new therapeutics is required to overturn these unmet medical needs. Recent studies highlighted the importance of gut microbiota in the development of mental disorders, including depression. Administration of several gut microbiota-modifying interventions like probiotics, such as Lactobacillus reuteri NK33, Lactobacillus paracasei PS23, Lactobacillus plantarum MTCC 9510 , Lactobacillus kefiranofaciens ZW3, Lactobacillus gasseri CP2305, Bifidobacterium breve UBBr-01, and Bifidobacterium infantis UBBI-01, and prebiotics, such as polyphenols, polysaccharides, and dietary fibers, exerted robust antidepressant-like phenotypes in animals by promoting the colonization of other beneficial microorganisms in the host. However, clinical outcomes of probiotics/prebiotics in human studies are still debatable and inconclusive. , …”
Section: Introductionmentioning
confidence: 99%
“…development, function, mood and cognition may be influenced by the symbiotic flora (30). The gut microbiota and CNS are connected through multiple bidirectional pathways involving neural, endocrine, and immune signaling, and dysbiosis of the gut flora can cause psychiatric disorders, such as depression (31)(32)(33).…”
Section: Intestinal Flora Dysbiosismentioning
confidence: 99%
“…These symbiotic flora synthesize a variety of vitamins essential for human growth and development, and also use protein residues to synthesize essential amino acids and participate in the metabolism of sugars and proteins, as well as promote the absorption of minerals such as iron, magnesium, and zinc and metabolize toxins ( 29 ). The brain and the gut are closely linked and various aspects of brain development, function, mood and cognition may be influenced by the symbiotic flora ( 30 ). The gut microbiota and CNS are connected through multiple bidirectional pathways involving neural, endocrine, and immune signaling, and dysbiosis of the gut flora can cause psychiatric disorders, such as depression ( 31 33 ).…”
Section: Cyclo-oxygen-ase-2 Roles In the Pathogenesis Of Depressionmentioning
confidence: 99%
“…The GBA consists sympathetic and parasympathetic branches of the central nervous system, neuroendocrine system, autonomic nervous system, enteric nervous system, gut and gut microbes, and their metabolites. Gut microbes transmit information through the enteric nervous system to the vagus nerve and then reach the central nervous system to affect psychological, cognitive, behavioral and neurological functions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%